Gamma camera calibration and validation for quantitative SPECT imaging with 177Lu. (June 2016) - D'Arienzo, M.; Cazzato, M.; Cozzella, M.L.; Cox, M.; D'Andrea, M.; Fazio, A.; Fenwick, A.; Iaccarino, G.; Johansson, L.; Strigari, L.; Ungania, S.; De Felice, P.
Abstract: Over the last years 177 Lu has received considerable attention from the clinical nuclear medicine community thanks to its wide range of applications in molecular radiotherapy, especially in peptide-receptor radionuclide therapy (PRRT). In addition to short-range beta particles, 177 Lu emits low energy gamma radiation of 113 keV and 208 keV that allows gamma camera quantitative imaging. Despite quantitative cancer imaging in molecular radiotherapy having been proven to be a key instrument for the assessment of therapeutic response, at present no general clinically accepted quantitative imaging protocol exists and absolute quantification studies are usually based on individual initiatives. The aim of this work was to develop and evaluate an approach to gamma camera calibration for absolute quantification in tomographic imaging with 177 Lu. We assessed the gamma camera calibration factors for a Philips IRIX and Philips AXIS gamma camera system using various reference geometries, both in air and in water. Images were corrected for the major effects that contribute to image degradation, i.e. attenuation, scatter and dead- time. We validated our method in non-reference geometry using an anthropomorphic torso phantom provided with the liver cavity uniformly filled with 177 LuCl3 . Our results showed that calibration factors depend on the particular reference condition. In general, acquisitions performed with the IRIX gamma camera provided good results at 208 keV, with agreement within 5% for all geometries. The use of a Jaszczak 16 mL hollow sphere in water provided calibration factors capable of recovering the activity in anthropomorphic geometry within 1% for the 208 keV peak, for both gamma cameras. The point source provided the poorest results, most likely because scatter and attenuation correction are not incorporated in the calibration factor. However, for both gamma cameras all geometries provided calibration factors capable of recovering the activity in anthropomorphic geometry within about 10% (range −11.6% to +7.3%) for acquisitions at the 208 keV photopeak. As a general rule, scatter and attenuation play a much larger role at 113 keV compared to 208 keV and are likely to hinder an accurate absolute quantification. Acquisitions of only the 177 Lu main photopeak (208 keV) are therefore recommended in clinical practice. Preliminary results suggest that the gamma camera calibration factor can be assessed with a standard uncertainty below (or of the order of) 3% if activity is determined with equipment traceable to primary standards, accurate volume measurements are made, and an appropriate chemical carrier is used to allow a homogeneous and stable solution to be used during the measurements. Highlights: We evaluated an approach to gamma camera calibration for SPECT imaging with 177 Lu. Accurately calibrated reference activity was used to maintain a low uncertainty in the calibration of the gamma camera. Calibration factors were assessed using various reference geometries, both in air and in water. We validated our method using an anthropomorphic phantom uniformly filled with 177 LuCl3 . The gamma camera calibration factor can be determined with a standard uncertainty below 3%. We recommend acquisitions only on the 177 Lu main photopeak (208 keV) in clinical practice.